Response characteristics of the pigeon's pretectal neurons to illusory contours and motion - Niu, Yu-Qiong (Blackwell Science Inc, 2006)
Misinterpretations of visual information received by the retina are called visual illusions, which are known to occur in higher brain areas. However, whether they would be also processed in lower brain structures remains unknown, and how to explain the neuronal mechanisms underlying the motion after-effect is intensely debated. We show by extracellular recording that all motion-sensitive neurons in the pigeon's pretectum respond similarly to real and illusory contours, and their preferred directions are identical for both contours in unidirectional cells, whereas these directions are changed by 90 deg for real versus illusory contours in bidirectional cells. On the other hand, some pretectal neurons produce inhibitory (excitatory) after-responses to cessation of prolonged motion in the preferred (null) directions, whose time course is similar to that of the motion after-effect reported by humans. Because excitatory and inhibitory receptive fields of a pretectal cell overlap in visual space and possess opposite directionalities, after-responses to cessation of prolonged motion in one direction may create illusory motion in the opposite direction. It appears that illusory contours and motion could be detected at the earliest stage of central information processing and processed in bottom-up streams, and that the motion after-effect may result from functional interactions of excitatory and inhibitory receptive fields with opposite directionalities.